ORGANIZATIONAL CULTURE AND DEMOGRAPHIC CHARACTERISTICS A LITERATURE REVIEW - Jelena Octavia (Jurnal Manajemen, 2016)
This paper explore the relationship between organizational culture and demographic characteristics. Organizational culture refers to a series of attitudes and behaviors adopted by employees of a certain organization, which affect its function and total well-being. Generally, demographic characteristics refers to age, gender, work level, and tenure. Some researchers add job rank, race/ethnicity, education level, and marital status for several industries. This paper use qualitative research and the research approach is literature review. The result of this review shows that demographic characteristics such as age and gender are most related to the organizational culture in the working environment and their relations with colleagues. Some research put job satisfaction and performance as a dependent variable, meanwhile organizational culture as an independent variable. Demographic characteristics mostly used as a moderator variable. Organization need to pay attention to individual demographic characteristics when choosing an organization member to fill the leadership level. Demographic characteristics in individuals will affect the success of the organization in achieving its mission vision. Organizations with certain characteristics and fit with the existing culture, then the individuals will feel comfortable and more productive in their work.   Keywords: Organizational Culture; Demographic Characteristics